1999
DOI: 10.2337/diabetes.48.5.1013
|View full text |Cite
|
Sign up to set email alerts
|

Sustained proliferation of PDX-1+ cells derived from human islets.

Abstract: Ex vivo expansion of human beta-cells is an important step toward the development of cell-based insulin delivery systems in type 1 diabetes. Here, we report that human pancreatic endocrine cells can be expanded through 15 cell doublings in vitro for an estimated total 30,000-fold increase in cell number. We believe that the cells resulting from these cultures are of beta-cell origin, since they uniformly express the transcription factor PDX-1 (STF-1, IDX-1, IPF-1), which is initially seen only in cells positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
98
3
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 0 publications
2
98
3
3
Order By: Relevance
“…Primary β-cells stimulated to enter the cell cycle quickly dedifferentiate and lose insulin expression [1], suggesting a tight inverse linkage between β-cell growth and differentiation. This study aimed to determine the mechanism underlying this.…”
Section: Introductionmentioning
confidence: 99%
“…Primary β-cells stimulated to enter the cell cycle quickly dedifferentiate and lose insulin expression [1], suggesting a tight inverse linkage between β-cell growth and differentiation. This study aimed to determine the mechanism underlying this.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, a great effort has been made to develop new methods for generating b-like cells in vitro, 2,3 despite of evidence that cultured b-cells have limited proliferative capacity and reduced insulin production. 4 Several attempts have been made to identify stem/progenitors cells within pancreatic tissue as a potential source for transplantable insulinproducing tissue. Unfortunately, the origin of new b-cells in adult pancreas is not known.…”
mentioning
confidence: 99%
“…Some in vivo studies suggested the presence of pancreatic progenitor cells within islets, 5 whereas others reported that new adult b-cells might rather originate from pre-existing b-cells. 6 Additional studies suggested that progenitor cells may reside within the pancreatic ductal epithelium [2][3][4][5][6][7] or in the acinar tissue. 8,9 Nevertheless, the exact nature and localization of adult pancreatic stem/ progenitor cells remains controversial [9][10][11][12][13][14][15][16] and their existence in vivo, at least in mice, has recently been questioned.…”
mentioning
confidence: 99%
“…Evidence supports the regeneration of adult mouse beta cells in vivo from both insulin-producing cells [1,2] and pancreatic duct cells [3], and recent analyses of autopsied human pancreatic tissue suggest that human islets may grow by beta cell replication [4]. However, assessment of beta cell proliferation in vitro is much harder, since the beta cell phenotype is rapidly lost [5,6], making it difficult to determine whether the loss of beta cell markers in the expanded cells reflects beta cell dedifferentiation, or beta cell death accompanied by expansion of pancreatic cells from a non-beta cell origin. In genetic lineage-tracing studies using islets from transgenic mice, the specific labelling of beta cells with a fluorescent protein produced under the control of an ubiquitous promoter allowed tracking of mouse beta cell fate in vitro [7].…”
Section: Gfp Green Fluorescent Proteinmentioning
confidence: 99%